Odpowiedzi

2010-02-09T18:35:10+01:00
-5 + - 9 = -14
-9 - - 5 = - 4
-5 * - 9 = -45
--5 * 9 = 45
-5 --9 = 4
-5 --9 = 4
-5:9 = -0,55
9:5 = 1,8
2010-02-09T18:37:41+01:00
A=-5 b=-9
rozwiąż :
a+b = -5+(-9) = -5-9=-14

b-a = -9-(-5) = -9+5 = -4

a*b = (-5)*(-9) = 45

(-a)*b = [-(-5)]*(-9) = 5*(-9) = -45

a-b = -5-(-9) = -5+9 = 4

a+(-b) - 5 +[-(-9)] = -5+9=-4

a:(-b) = -5:[-(-9)] = -5:9= - 5/9 (ułamek)

(-b):(-a) = [-(-9)]:[-(-5)] = 9:5 = 9/5 (ułamek) = 1,8
2010-02-09T18:40:12+01:00
-5 + (-9) = -14
-9 - (-5) = -4
-5 * (-9) = -45
(-5) * -9 = -45
-5 - (-9)= 4
-5 + (-9)= -14
-5 : (-9)= -14
(-9) : (-5)= - 1.8